Self-esteem and Social Media Dependency: a Structural Equation Modelling Approach to Comparing Primary Welsh and Non-Welsh Speakers - RICHARD JONES (Trends in Psychology, 2023)
The current study examined the impact of using social media in English on associations between social media dependency and self-esteem, depression, social anxiety, and loneliness for Welsh speakers. A total of 836 pupils (317 Welsh speakers; 519 non-Welsh speakers), with a mean age of 13.44 (± .943), attending state-maintained Welsh/bilingual-medium secondary schools throughout Wales, completed scales on social media dependency, self-esteem, depression, social anxiety, and loneliness. A structural equation model approach found that whenever social media dependency was the predictor, its hypothesized associations with depression, loneliness, social anxiety, and self-esteem were stronger for Welsh speakers relative to non-Welsh speakers. The results suggest that a perceived or actual marginalization of a minority language within the social media domain might negatively impact minority language speakers’ self-esteem levels, which potentially impacts related psychological constructs.